Evolution of hybrid systems for treatment of effluents from the pesticide production industry. - Goodwin, Lindsey Marie (Cranfield University, 2017)
The pesticide production industry generates a high strength wastewater containing a range of toxic pollutants (2,4-dichlorphenoxy acetic acid: 2,4-D; 4-(2,4-dichlorphenox) propionic acid: 2,4-DP; 4-(2,4-dichlorophenox) butyric acid: 2,4-DB; 2,4-dichlorophenol: 2,4-DCP; 2,4,6-trichlorophenol: 2,4,6-TCP; 4-chlororthocresol: PCOC; 4-chloro-2-methyl phenoxyacetic acid: MCPA, 4-(4-chloro-2-methylphenoxy) butyric acid: MCPB and 2-(4-chloro-2-methylphenoxy) propionic acid: MCPP). These pesticides can enter the natural environment and water sources if not removed in a wastewater treatment plant. Treated effluents are regulated by legislation such as the Water Framework Directive (WFD). The organic matter and pesticides concentrations in the wastewater were highly variable across the 12 sampling campaign carried out. These results were expected, as the pesticide production facility manufactures different formulations at different intervals of time. The biochemical oxygen demand (BOD) and chemical oxygen demand (COD) concentrations ranged from 5101-18000 mg/L and 18675-47763 mg/L, respectively. The pesticides average concentrations for 2,4-DCP were high at 58.96 mg/L, followed by MCPA at 32.45 mg/L, PCOC with 21.91 mg/L, 2,4-D at 13,94 mg/L and MCPP at 7.58 mg/L. On the other side the average concentrations for 2,4-DB and 2,4,6-TCP were >5 mg/L and the average concentrations for 2,4-DP and MCPB were <1 mg/L. When evaluating different treatment options to design a hybrid system to treat the pesticide production industry wastewater it was clear that a biological treatment process should be considered due to the high BOD and COD. Anaerobic treatability tests indicated that the wastewater was toxic to organism present in anaerobic digested sludge, as no methane production was observed at dilutions >1%. Aerobic respirometry tests showed this wastewater was toxic to activated sludge microorganisms at dilutions >25%. Nevertheless, when testing the wastewater diluted to 25%, it was observed that the addition of nutrients (1.7 g/L NH4 and 0.23 g/L PO4) and alkalinity (and 0.1 g/L) enhanced the biological degradation, with pesticide removals of 63% for phenoxy acids (MCPB, MCPA, PCOC, MCPP), 34% for 2,4,6-TCP and 17% for dichloro acids (2,4-D, 2,4-DP, 2,4-DB, 2,4DCP).. Acclimatisation studies were inconclusive. The physical/chemical characterization of the key pollutants present in the pesticide production wastewater indicates their likelihood to be adsorbed (molecular weight >170 mg/L and Log Kₒw >2.5). Tests completed with granular activated carbon (GAC) indicated high adsorption capacity for these pollutants as 1 g/L GAC removed 100% of the phenoxy acids, 2,4,6-TCP and dichloro acids within 24h. Lab-scale column tests were completed with pesticides breaking through between 599-1374 bed volumes (BV) when using 3-30 minutes EBCT. Advanced oxidation processes (AOPs) showed no removal of pesticides when treating the wastewater with Fenton process even at high doses of H₂O₂ (12500 mg/L) and Fe²⁺(20 mg/L) Other tests were completed with UV/H₂O₂ using a dose of 1250 mg/L H₂O₂ and a UV intensity of 3 mW/cm² but low 30% total pesticides removal was also observed. On the other side, UV photolysis was a shown to be efficient at removing the pesticides without the presence of H₂O₂. The GAC-biological hybrid system showed that after GAC treatment the pesticide production wastewater was not toxic to the aerobic microorganisms at 75% wastewater dilution. After 552 BV GAC and biological treatment, removal efficiencies were significant with overall pesticide removals of 86% (phenoxy acids), 98% (dichloro acids) and 83% (2,4,6-TCP). Nevertheless, the effluent quality produced by this process would not bet high enough to achieve the limits described in the WFD and the GAC would need frequent regeneration, leading to high operational costs. A number of hybrid systems (granular activated carbon, membrane bioreactor and ultraviolet photolysis) were also investigated. The MBR-GAC pilot-plant showed very effective especially after dosing with additional nutrients and alkalinity. After diluting the wastewater to 25%, to prevent toxicity to the MBR process, and GAC, the removals reached 88% for COD, 72% for BOD and 86-99% for pesticides. Photolysis with UV showed promising results to replace the GAC, as the MBR-UV system achieved a total pesticides removal of 99-100%. The MBR-UV hybrid system generated an effluent with 5 μg/L MCPA, 1 μg/L MCPB, 7 μg/L MCPP, 22 μg/L PCOC, 39 μg/L 2,4-D, 0.75 μg/L 2,4-DP, 0.37 μg/L 2,4-DB, 5 μg/L 2,4-DCP and 5 μg/L 2,4,6-TCP. Nevertheless, even with high effectiveness of the MBR and UV system the effluent did not reach the discharge limits to meet WFD annual average environmental quality standards (EQS) for 2,4-D (0.3 μg/L) and MCPA (2 μg/L), just the EQS for 2,4-DCP (20μg/L) and MCPP (18 μg/L) would be met. The EQS are set for environmental water quality and could be met if the treated wastewater is discharged to a water body that ensures 1:150 dilution, assuming that no 2,4-D is present in receiving water body.
Keywords: Activated carbon; activated sludge; advanced oxidation processes; biological treatment; chlorophenoxy herbicides; Fenton process; UV/H₂O₂; industrial wastewater treatment